PHARMACOTHERAPY IN ELDERLY NEUROPATHIC PAIN - Eko P, Thomas (Medicina; Vol 44 No 1 (2013): Januari 2013, 2013)
Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 The incidence of pain increases with age. Neuropathic pain are common in elderly patients and pose challenges in both their diagnosis and treatment. The most common neuropathic pain in elderly are radiculopathy due to foraminal or spinal stenosis, diabetic neuropathy , and postherpetic neuralgia. Pain in the elderly is often unrecognized and undertreated. The main problem with pain in older adults relates to impaired quality of life secondary to pain which may be expressed by depression (including increased suicide risk), anxiety, sleep disruption, appetite disturbance, and weight loss, cognitive impairment, and limitations in the performance of daily activities. Pain management in elderly patients requires a different perspective from that of younger patients. Causes, comorbidities, and responses to both pain and its treatment differ between young healthy and older patients. Effective pain management in elderly patients should include both pharmacologic and nonpharmacologic strategies. Pharmacological approaches are the first line of pain management in older person for neuropathic pain. Pharmacologic strategies call for administration of nonopioid analgesics, opioid analgesics, and adjuvant medication. Polypharmacy, drug-drug and drug-disease interactions, age-associated changes in drug metabolism, and the high frequency of adverse drug reactions need to be carefully considered in using medications in this population /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: pain management, neuropathic pain, elderly, pharmacological therapy